Photonic nanojet of a Gaussian beam illuminated low refractive index microsphere in air: A comprehensive variation of parameters. (May 2022) - Gašparić, Vlatko; Ristić, Davor; Mayerhöfer, Thomas G.; Baran, Nikola; Gebavi, Hrvoje; Maksimović, Aleksandar; Ivanda, Mile
Highlights: The photonic nanojet (PNJ) properties and parameters showed complex dependency. The incident beam position can be tuned to achieve two different types of PNJs. Type 1 has lower intensity and larger size, type 2 has high intensity and smaller size. The PNJ intensity generally is higher when microsphere and beam sizes are comparable. As microsphere size increases, the width and length of the PNJ increase. As the beam size increases, the width and length decrease for type 1, and increase for type 2. When the wavelength is decreased, the PNJ intensity and confinement increase. Abstract: A photonic nanojet (PNJ) is a narrow beam of concentrated light emerging from the illuminated micro-scattering objects, which has attracted a lot of attention lately. However, so far the variation and the properties of the PNJ of a microsphere have been computationally investigated in a limited scope and mostly for plane wave as a source. Within the framework of the Generalized Lorenz-Mie theory (GLMT), a large-scale investigation of the PNJ properties (intensity, position, length and width) and their dependence on the parameters which influence the PNJ (beam wavelength, beam size, beam position and microsphere size) is presented. The calculations are carried out for more than 400 000 configurations of parameters, with Gaussian beam source. Computations show that each parameter plays an important role in the PNJ formation. The influence of each of the parameters and their complex interplay is studied in detail. Depending on the beam position, PNJs are classified into two types, with different characteristics and possible applications. We believe this systematic and comprehensive presentation of the widest range of PNJs so far will advance the knowledge of this phenomenon, and serve as a reference for tailoring any PNJ according to one's needs and applications. Graphical abstract: Table of content Image, graphical abstract